Chemical Profile and Toxicity of Fresh and Dry leaves of the Essential Oils of Vetiveria zizanioides (L.) Nash. From Southwest Nigeria - Olosunde Peace; Yeye Emmanuel; Aboaba Sherifat (Recent Trends in Cosmetics, 2024)
The fresh and dry leaves of Vetiveria zizanioides (L.) Nash (Gramineae) plant was collected, air dried and authenticated at the University of Ibadan Herbarium with voucher number: UIH-23237. The plant's dried, fresh leaves were hydro distilled in a Clevenger device to extract the essential oils. The oils were characterized by Gas Chromatography-Mass Spectrometry (GC – MS) while the toxicity of the essential oils was tested using brine shrimps’ lethality assay. The percentage yields of fresh and dry leaf oils were 0.045 %v/w and 0.42 %v/w respectively. Thirty-eight (38) chemical compounds were identified in the fresh leaf sample of V. zizanioides. The major components were 8-Cedren-13-ol (12.24%), Spathulenol (7.01%), 6-(3-acetyl-2-methylcyclopropen-1-yl)-6-methylheptan-2-one (4.95%), β-Patchoulene (3.68%), 9H-Cycloisolongifolene, 8-oxo- (3.65%). Thirty-four (34) compounds were found in all. Thirty-four (34) chemicals were found in the essential oil of V. zizanioides dry leaf. The major components were 6-(3-Acetyl-2-methyl-1-cyclopropen-1-yl)-6-methyl-2-heptanone (13.73%),(1aR,4aR,7S,7aR,7bR)-1,1,7-Trimethyl-4-methylenedecahydro-1H-cyclopropa[e]azulen-7-ol (12.07%), (-)-globulol (9.05%), 1,1,4,7 tetramethyldecahydro1Hcyclopropa[e]azulen4ol,[1aR(1a.alpha.,4.beta.,4a.beta.,7.alpha.,7a.beta.,7b.alpha) (7.90%), hibaene (6.26%), hexahydrofarnesylacetone (5.59%), bicyclo[9.3.1]pentadeca-3,7-dien-12-ol (2.59%), β-Ionone (2.41%). Copaene, α-muurolene, δ-cadinol, phytol and bicyclo [9.3.1] pentadeca-3, 7-dien-12-ol were found to be the common constituents in both fresh and dry leaf essential oils. The cytotoxicity results of both essential oils showed that both oils are extremely toxic with LC50 of 10 ppm. The identified compounds from the dry and the fresh samples of V. zizanioides may be responsible for the cytotoxic activities of the plant while the variations in the constituents of the two oils are largely due to different sample preparation conditions.
Keywords: 8-Cedren-13-ol; Cytotoxicity; Gas Chromatography-Mass Spectrometry; Vetiveria zizanioides; Volatile oil